Stark broadening of hydrogen/deuterium spectral lines by a relativistic electron beam: analytical results and possible applications to magnetic fusion edge plasmas. (30th January 2018) - Oks, E; Sanders, P
Abstract: We present a theory of the Stark broadening of hydrogen/deuterium spectral lines by a relativistic electron beam (REB). The theory is developed analytically by using an advanced formalism. We discuss the possible application of these analytical results to magnetic fusion edge plasmas, taking into account also the major outcome of the interaction of a REB with plasmas: the development of strong Langmuir waves.